EFEKTIFITAS ASAM HUMAT DAN ARANG AKTIF TEMPURUNG KELAPA DALAM MENGADSORBSI RESIDU INSEKTISIDA ENDOSULFAN DI DALAM TANAH LATOSOL BOGOR - Lany Nurhayati; RTM Sutamihardja; Linggar Rudiarto (Universitas Nusa Bangsa, 2014)
Effectiveness of Humic Acid and Active Charcoal of Coconut Shell on Adsorbtion the Residual Insecticide Endosulfan in Latosol Soil, Bogor In the study of humic acid and coconut shell activated charcoal (AATK) soaked in Humic Acid (5% and 10%) was left to dry for three days. The soil weighed as much as 10 grams mixed with activated charcoal soaked humic acid 5% and 10% by series concentration of 500 ppm; 1000 ppm and 1500 ppm, then added 20 mL of distilled water in each row shaken for one night, the soil was conditioned by the concentration of the insecticide endosulfan series: 12:05, 0,1, 0,2, 0,4, 0,8 and 1 ppm, did incubation. Example decanted, added 10 mL of acetone pa, filtered and then added with acetone as much as 10 mL, the extract was evaporated to 1 mL, then added by 10 mL acetone gradually. Results extract transferred into sample vials to be tested by using GC. Based on the analysis, it found residues of the insecticide endosulfan in Bogor Latosol soil with a concentration of 0.0005 ppm. The addition of coconut shell activated charcoal individually had a significant effect in reducing the content of endosulfan in soil, while the addition of humic acid individually did not have an appreciable impact in reducing residues of endosulfan in soil latosol. Insecticide endosulfan residues were able to be adsorbed by AATK and humic acid was 500 ppm and 10% (A500H10) of 0,12178a ppm. The combination AATK and humic acids provide a real impact on the content of endosulfan residues in the soil latosol Bogor that could adsorb residual content in the soil.Keywords: Organochlorines Insecticide Endosulfan, Humic Acid, Coconut Shell Charcoal On Land Latosol Bogor ABSTRAK Pada penelitian asam humat dan arang aktif tempurung kelapa (AATK) direndam dalam Asam Humat (5% dan 10%) dibiarkan sampai mengering selama tiga hari.Tanah ditimbang sebanyak 10 gram dicampurkan dengan arang aktif yang sudah direndam asam humat 5% dan 10% dengan deret konsentrasi 500 ppm; 1000 ppm dan 1500 ppm, kemudian ditambahkan 20 mL aquades pada masing deret dikocok selama satu malam, tanah dikondisikan dengan deret konsentrasi insektisida endosulfan : 0,05, 0,1, 0,2, 0,4, 0,8 dan 1 ppm, lakukan inkubasi. Contoh didekantasi, ditambahkan aseton pa 10 mL, disaring kemudian ditambahkan dengan aseton sebanyak 10 mL, hasil ekstrak dievaporasi sampai 1 mL, kemudian ditambahkan aseton sebanyak 10 mL secara bertahap. Hasil Ekstrak dipindahkan kedalam botol sampel untuk diuji dengan menggunakan GC. Berdasarkan hasil analisis, masih ditemukan residu insektisida endosulfan di tanah Latosol Bogor dengan konsentrasi 0,0005 ppm. Penambahan arang aktif tempurung kelapa secara individual memiliki pengaruh yang cukup signifikan dalam mengurangi kandungan endosulfan dalam tanah, sedangkan penambahan asam humat secara individual tidak memiliki pengaruh yang cukup besar dalam mengurangi kandungan residu endosulfan dalam tanah latosol. Residu insektisida endosulfan terbaik mampu diadsorbsi oleh AATK dan asam humat adalah 500 ppm dan 10% (A500H10) sebesar 0,12178a ppm. Kombinasi AATK dan asam humat memberikan pengaruh yang nyata terhadap kandungan residu endosulfan didalam tanah latosol bogor sehingga dapat mengadsorbsi kandungan residu didalam tanah.Kata Kunci: Insektisida Organoklorin Endosulfan, Asam Humat, Arang Aktif Tempurung Kelapa, Tanah Latosol Bogor